Establishment of PDX‐derived salivary adenoid cystic carcinoma cell lines using organoid culture method. Issue 1 (7th October 2020) - Takada, Kentaro; Aizawa, Yoshihiro; Sano, Daisuke; Okuda, Ryo; Sekine, Keisuke; Ueno, Yasuharu; Yamanaka, Shoji; Aoyama, Jun; Sato, Kaname; Kuwahara, Tatsu; Hatano, Takashi; Takahashi, Hideaki; et al.
Abstract: To generate a reliable preclinical model system exhibiting the molecular features of salivary adenoid cystic carcinoma (ACC) whose biology is still unclear due to the paucity of stable cell cultures. To develop new in vitro and in vivo models of ACC, the techniques of organoid culture and patient‐derived tumor xenograft (PDX), which have attracted attention in other malignancies in recent years, were applied. Tumor specimens from surgically resected salivary ACC were proceeded for the preparation of PDX and organoid culture. The orthotopic transplantation of patient‐derived or PDX‐derived organoids was demonstrated into submandibular glands of NSG mice and those histology was evaluated. PDX‐derived organoid cells were evaluated for the presence of MYB ‐mediated fusion genes and proceeded for in vitro drug sensitivity assay. Human ACC‐derived organoids were successfully generated in three‐dimensional culture and confirmed the ability of these cells to form tumors by orthotopic injection. Short‐term organoid cell cultures from two individual ACC PDX tumors were also established that maintain the characteristic MYBL1 translocation and histological features of the original parent and PDX tumors. Finally, the establishment of drug sensitivity tests on these short‐term cultured cells was confirmed using three different agents. This is the first to report an approach for the generation of human ACC‐derived organoids as in vitro and in vivo cancer models, providing insights into understanding of the ACC biology and creating personalized therapy design for patients with ACC. Abstract : What's new? The biological underpinnings of salivary adenoid cystic carcinoma (ACC) remain largely unknown, owing to a lack of preclinical model systems. In this study, the authors describe the successful generation of human salivary ACC cell lines from organoid culture and the subsequent development of an in vivo salivary ACC mouse model. The orthotopic xenograft mouse model was established efficiently from ACC organoid cells from patient‐derived xenografts (PDX). Short‐term cultures of PDX‐derived ACC organoid cells further were amenable for in vitro drug‐sensitive studies with several agents. This novel approach could be useful for investigating personalized therapies for patients with salivary ACC.